New insights into Fe localization in plant tissues - Roschzttardtz, Hannetz; Conéjéro, Geneviève; Divol, Fanchon; Alcon, Carine; Verdeil, Jean-Luc; Curie, Catherine; Mari, Stephane (Frontiers in Plant Science, 2013)
Deciphering cellular iron (Fe) homeostasis requires having access to both quantitative and qualitative information on the subcellular pools of Fe in tissues and their dynamics within the cells. We have taken advantage of the Perls/DAB Fe staining procedure to perform a systematic analysis of Fe distribution in roots, leaves and reproductive organs of the model plant Arabidopsis thaliana, using wild-type and mutant genotypes affected in iron transport and storage. Roots of soil-grown plants accumulate iron in the apoplast of the central cylinder, a pattern that is strongly intensified when the citrate effluxer FRD3 is not functional, thus stressing the importance of citrate in the apoplastic movement of Fe. In leaves, Fe level is low and only detected in and around vascular tissues. In contrast, Fe staining in leaves of iron-treated plants extends in the surrounding mesophyll cells where Fe deposits, likely corresponding to Fe-ferritin complexes, accumulate in the chloroplasts. The loss of ferritins in the fer1,3,4 triple mutant provoked a massive accumulation of Fe in the apoplastic space, suggesting that in the absence of iron buffering in the chloroplast, cells activate iron efflux and/or repress iron influx to limit the amount of iron in the cell. In flowers, Perls/DAB staining has revealed a major sink for Fe in the anthers. In particular, developing pollen grains accumulate detectable amounts of Fe in small-size intracellular bodies that aggregate around the vegetative nucleus at the binuclear stage and that were identified as amyloplasts. In conclusion, using the Perls/DAB procedure combined to selected mutant genotypes, this study has established a reliable atlas of Fe distribution in the main Arabidopsis organs, proving and refining long-assumed intracellular locations and uncovering new ones. This “iron map” of Arabidopsis will serve as a basis for future studies of possible actors of iron movement in plant tissues and cell compartments.